Adsorption and Desorption of Organic Molecules From Thin Cellulose Films - Henögl, Elias; Haberl, Viktoria; Ablasser, Jakob; Schennach, Robert (Frontiers in Materials, 2019)
The debate on environmental effects of everyday packaging materials has long reached the scientific community. The quest is on to design cheap, but also sustainable and eco - friendly packaging solutions. A hot contestant material within the application is the ever present wood based paper. In addition to meeting logistic requirements, paper packaging must protect the packaged goods from environmental influences, while keeping aroma molecules in the food. To quantify both aspects in depth, exploration of adsorption of organic molecules on paper is required. As paper is a rather complex material, adsorption and desorption experiments can be notoriously difficult to interpret. This paper will demonstrate that the adsorption of organic molecules on a cellulose surface can be investigated simply? by using temperature programmed desorption (TPD) experiments. The experiments show that both non-polar and polar molecules (n-decane and deuterated methanol) readily adsorb onto cellulose films. During desorption one finds the polar molecule bound to the cellulose surface more heavily, effectively oder doch strongly? than the non-polar molecule.